Boron "gluing" nitrogen heteroatoms in a prepolymerized ionic liquid-based carbon scaffold for durable supercapacitive activity. Issue 5 (18th December 2020) - Miao, Ling; Duan, Hui; Zhu, Dazhang; Lv, Yaokang; Gan, Lihua; Li, Liangchun; Liu, Mingxian
Abstract : Doped boron atoms are bridged to glue more electroactive nitrogen sites on the carbon surface, and the high binding energy of the consequent B–C bonds further consolidates the porous carbon scaffold for durable ion/electron transfer. Abstract : The incorporation of heterogeneous active sites into the carbon scaffold offers great potential to break the energy limitation in state-of-the-art supercapacitors, but rich heteroatomic motifs essentially thwart the scaffold firmness, leading to poor power/cycling durability under wide operational voltages/temperatures. Herein, a high-crosslinking prepolymerized ionic liquid p [ABA- co -MA][PA] network is designed to initially trap volatile heterogeneous segments during annealing, and gives the final N/B/O-doped porous carbon scaffolds (CPILs) with rich electroactive sites and pre-supposed structural superiorities. B-doped sites on the scaffold are bridged to glue/fix more electroactive N (4.21–9.05 at%) compared with the solely N-doped sample (2.87 at%), and the high binding energy of the consequent B–C bonds further consolidates the porous carbon scaffold for durable ion/electron transfer. As a result, the highly electroactive CPIL surface with 2629 m 2 g −1 surface area and 23.13 at% electroactive N/B/O enables a large specific capacitance (359 F g −1 @ 0.5 A g −1 ) and slight capacitance fade (19% @ 20 A g −1 ) in H2 SO4 electrolyte, as well as maximized electrode capacitance up to 211 F g −1 at 3.5 V in EMIM-BF4 owing to the strong electrosorption ability of the electrolyte ions. Moreover, the CPIL-loaded symmetric supercapacitor in TMA-BF4 /EMIM-BF4 electrolyte yields a high energy output of 116 W h kg −1 @ 400 W kg −1 under a high potential of 4 V, durable service life (98.2% retention after 10 000 cycles) and wide temperature applicability from −3.5 to 82 °C. This work highlights the comprehensive improvement of multi-heteroatom doping in supercapacitive activity and durability, which provides an appealing strategy to enrich various applications.